2007
DOI: 10.2353/ajpath.2007.070146
|View full text |Cite
|
Sign up to set email alerts
|

Plasmin-Cleaved β-2-Glycoprotein 1 Is an Inhibitor of Angiogenesis

Abstract: beta-2-Glycoprotein 1, an abundant plasma glycoprotein, binds anionic cell surfaces and functions as a regulator of thrombosis. Here, we show that cleavage of the kringle domain at Lys317/Thr318 switches its function to a regulator of angiogenesis. In vitro, the cleaved protein specifically inhibited the proliferation and migration of endothelial cells. The protein was without effect on preformed endothelial cell tubes. In vivo, the cleaved protein inhibited neovascularization into subcutaneously implanted Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 54 publications
1
33
0
5
Order By: Relevance
“…However, lack of using purified material makes it difficult to assume the concentration of nicked ␤2GPI generated in this study. Sakai et al 29 reported that 4 M nicked ␤2GPI inhibited endothelial cell migration, proliferation, and neovascularization into subcutaneous implants that contain VEGF. Intraperitoneal injection of nicked ␤2GPI also inhibited growth of orthotopically injected tumors in a murine prostate cancer model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lack of using purified material makes it difficult to assume the concentration of nicked ␤2GPI generated in this study. Sakai et al 29 reported that 4 M nicked ␤2GPI inhibited endothelial cell migration, proliferation, and neovascularization into subcutaneous implants that contain VEGF. Intraperitoneal injection of nicked ␤2GPI also inhibited growth of orthotopically injected tumors in a murine prostate cancer model.…”
Section: Discussionmentioning
confidence: 99%
“…At relatively high concentrations more than 1 M, both intact and nicked ␤2GPI inhibited HUVEC migration and tube formation ( Figures 4B,5B), being relevant to the previous reports. 29,30 In these functional assays, nicked ␤2GPI exerted dual effect in the presence of AS4.5; at the lower concentrations, nicked ␤2GPI works as an AS4.5 inhibitor, whereas it works as an angiogenesis inhibitor at the higher concentrations. In the last part of this study, we confirmed that nicked ␤2GPI suppresses the antiangiogenic effect of AS4.5 in vivo ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…90 Proteolytic cleavage of HMWK can also generate 2-chain HMWK that inhibits angiogenesis. 91 Furthermore, cleavage of ␤ 2 GPI by plasmin 92 and polymorphonuclear neutrophil-derived proteases 93 has been shown to regulate the ability of ␤ 2 GPI to exhibit antiangiogenic and antibacterial activities. Similarly, cleavage of HRG by plasmin and other proteases has been proposed as a potential mechanism for the generation of antiangiogenic and antimicrobial fragments.…”
Section: Heparin Bindingmentioning
confidence: 99%
“…12 In addition, ␤ 2 -GPI also exerts antiangiogenic and antitumor activities. 13,14 Despite these activities, the main function of ␤ 2 -GPI is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, ␤ 2 -GPI also exerts antiangiogenic and antitumor activities. 13,14 Despite these activities, the main function of ␤ 2 -GPI is unknown.␤ 2 -GPI is composed, like complement factor H and factor H-related protein 1, of consecutive short consensus repeat elements (SCRs), also called complement control protein modules, each approximately 60 amino acids in size. 15 These repeats are frequently found in proteins with complement-regulatory functions.…”
mentioning
confidence: 99%